LAPAROSCOPIC VERSUS OPEN APPENDECTOMY FOR TREATMENT OF ACUTE APPENDICITIS - OUR EXPIRIANCE - Jovanović, Bojan (Acta medicae Medianae, 2023)
Acute appendicitis is one of the most common abdominal urgently intervention. Open appendectomy has been a standard procedure for acute appendicitis more than 100 years. But in last 20 years, after many studies, laparoscopic appendectomy was taking position of gold standard in solving od acute appendicitis . The main goal of our study was to compare results of open and laparoscopic appendectomies with regards about intrahospital stay, time of operation, postoperative complications and postoperative pain.All the patients who underwent open or laparoscopic appendectomy in the period from June 2020 untill June 2022 in Center of minimal invasive surgery and Emergency Center University Clinical Center Nis, Serbia. Total number of 260 patients were enrolled and submitted to retrospective analysis.260 patients where laparoscopic or open appendectomy was performed were retrospecively analised. Groups were demographically similar and there was no significante difference between age structure and gender distribution (t=0,927; p=0,355). There was no significante statistical difference in intraoperative findings among two groups (χ2=4,085; p=0,130). Average time of operation was the same in both groups (Z=0,214; p=0,831).Number of days of intrahospital stay was shorter in patients who has been performed by laparoscopic appendectomy (Z=10,615; p
Keywords: open appendectomy, laparoscopic appendectomy, acute appendicitis